Child Migrant Health: The Role of Pediatric Surgery in the Migrants' Route across Balkan Countries to North-West Europe - Marjanovic, Zoran; Raicevic, Maja; Slavkovic, Andjelka; Zivanovic, Dragoljub; Filipovic, Ivan; Bojovic, Nikola (European Journal of Pediatric Surgery, 2019)
Introduction Child migrants are the most vulnerable population, prone to various health conditions due to trauma and the bad living conditions that they experience during their migration. The objective of this study was to determine the pediatric surgical conditions of migrant children treated in our hospital on their way toward North-West Europe.Materials and Methods A retrospective analysis was performed on all admitted migrants in one tertiary and one secondary level hospital from 2016 to 2018. Only migrant children with surgical issues who had been hospitalized or treated in outpatient clinics were included in the study.Results There were 47 migrants admitted to hospitals and outpatient clinics; 32 from Afghanistan, 11 from Iraq, 1 from Syria, 2 from Iran, and 1 from Algeria. There were 27 boys and 20 girls, average age 7.96 years (range: 3 months–17 years). The average length of hospitalization was 14.1 days (range: 1–48), and average stay in the intensive care unit (ICU) was 7.4 days (range: 1–15). There were 29 migrants treated in outpatient clinics, and 18 were hospitalized. The cause of seeking surgical treatment was trauma in 33 and non-traumatic surgical problems in 14. The most common types of trauma were isolated fractures which occurred in one, followed by isolated head injury in eight. Polytrauma occurred in five. A lethal outcome occurred in one 9-year-old boy from Afghanistan due to severe polytrauma.Conclusion Trauma, predominantly fractures and head injuries, was the leading cause of morbidity in migrant children treated in these two hospitals.
Keywords: child migrants; pediatric surgery; trauma